Vector-Borne Agents in Species of Silky Anteater (Cyclopes Gray, 1821) from South America - Pedro Henrique Cotrin Rodrigues; João Paulo Soares Alves; Flávia Regina Miranda; Cesar Rojano; Júlia Angélica Gonçalves Silveira (Pathogens, 2025)
Cyclopes, the smallest of all known anteaters, has an insectivorous diet and is arboreal, rarely descending to the ground. There are scarce reports on diseases and pathogenic agents affecting this taxon. Hemopathogens are pathogenic agents that inhabit the blood of various vertebrate species. Protozoa such as Trypanosoma spp., Leishmania spp., Hepatozoon spp., and members of the order Piroplasmida, as well as hemoplasmas and Rickettsial bacteria of the genera Anaplasma and Ehrlichia, are among the most important in this group. The transmission of these pathogens generally occurs through arthropod vectors, which act as intermediate hosts. In addition, infections caused by hemopathogens can have adverse effects on host health, contributing to population declines in susceptible species. This study investigated infection by protozoa and hemotropic bacteria in blood samples from free-ranging silky anteaters from Brazil, Peru, and Colombia using molecular detection methods. Sixteen samples were obtained during expeditions conducted in these countries. DNA was extracted from blood samples, and PCR assays were performed to detect parasites from the order Piroplasmida, Hepatozoon spp., trypanosomatid agents including Leishmania spp., Trypanosoma evansi, T. cruzi, and T. vivax, as well as hemotropic bacteria of the genera Ehrlichia, Anaplasma, and Mycoplasma sp. Nucleotide sequencing was performed on positive samples. Of the total samples analyzed, 62.5% (10/16) tested positive for hemotropic Mycoplasma, 50% (8/16) for T. evansi, and 6.2% (1/16) for T. cruzi. There is a significant gap in knowledge regarding the diversity of hemopathogens affecting the genus Cyclopes, and future studies are needed to understand how these infections may impact the health of individuals.